2018
DOI: 10.1039/c8tc03936d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy regulation and its high frequency response mechanism in microwave ceramics

Abstract: This article reports a new research method for oxygen vacancy regulation in microwave ceramics and its high frequency response mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…33 Meanwhile, the substitution of donor Nb 5+ for Ti 4+ provides excess electrons, which contributes to inhibiting the formation of oxygen vacancies. 34 The decreased concentration of oxygen vacancies inhibits mass transportation during the sintering process, resulting in a decreased grain size. 35 The decreased average grain size contributes to the improvement of BDS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33 Meanwhile, the substitution of donor Nb 5+ for Ti 4+ provides excess electrons, which contributes to inhibiting the formation of oxygen vacancies. 34 The decreased concentration of oxygen vacancies inhibits mass transportation during the sintering process, resulting in a decreased grain size. 35 The decreased average grain size contributes to the improvement of BDS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Ti-containing systems, it was commonly found that the reduction of Ti 4+ ions brought about the deterioration of Qf values. [31][32][33] Similarly, the electron ionized from oxygen vacancy during the sintering process would be bonded to V 5+ . The defect equations were written as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The Qf reached 56 660 GHz at 740°C, was reduced with an increase in ST. In Ti‐containing systems, it was commonly found that the reduction of Ti 4+ ions brought about the deterioration of Qf values 31‐33 . Similarly, the electron ionized from oxygen vacancy during the sintering process would be bonded to V 5+ .…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of oxygen vacancy, relative density, and decrease in damping behavior would influence the Q×f value of Li 2 ZnTi 3 O 8 -x wt% Nb 2 O 5 [270]. To trace the dielectric response of lattice vibration, the response process of dielectric loss in Li 2 ZnTi 3-x M x O 8 (M = Al 3+ , Nb 5+ , (Al 0.5 Nb 0.5 ) 4+ , (Zn 1/3 Nb 2/3 ) 4+ , and (Li 1/4 Nb 3/4 ) 4+ ) was discussed systematically containing the conduction loss and lattice vibration loss [271]. The conduction loss which acts at frequency lower than terahertz is neglectful by researchers concentrating on MWDCs, while AC impedance analysis was used to identify the effect of dopants and the mechanism of conduction loss in this system.…”
Section: Rock-salt Structurementioning
confidence: 99%